PENGARUH RETURN ON EQUITY, DEBT TO EQUITY RATIO DAN CURRENT RATIO TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sheila; Hamida Sari Siregar (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Debt to Equity Ratio, and Current Ratio on Dividend Policy in companies listed on the Indonesia Stock Exchange. The population consists of 22 companies, with a sample of 8 companies observed over a four-year period (2021–2024), resulting in 32 observations. The data were analyzed using multiple linear regression. The results indicate that partially, Return on Equity does not have a significant effect on Dividend Policy, as evidenced by a tvalue of 1.335, which is lower than the ttable value of 2.045. Similarly, Debt to Equity Ratio does not have a significant effect on Dividend Policy, with a tvalue of 0.408, which is also lower than the ttable value of 2.045. In contrast, Current Ratio has a significant effect on Dividend Policy, with a tvalue of 2.987, which is higher than the ttable value of 2.045. Simultaneously, Return on Equity, Debt to Equity Ratio, and Current Ratio have a significant effect on Dividend Policy, as indicated by an F-value of 3.608, which exceeds the F-table value of 2.95. The coefficient of determination shows that Return on Equity, Debt to Equity Ratio, and Current Ratio explain 20.2% of the variation in Dividend Policy, while the remaining 79.8% is explained by other variables not included in this study. Keywords: Return on Equity, Debt to Equity Ratio, Current Ratio, Dividend Policy   Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh secara parsial dan simultan Return On Equity, Debt to Equity Ratio dan Current Ratio Terhadap Kebijakan Dividen pada Perusahaan yang Terdaftar di Bursa Efek Indonesia. Jumlah populasi 22 perusahaan dan sampel sebanyak 8 perusahaan dikali dengan 4 tahun pengamatan (2021-2024) menjadi 32 pengamatan. Analisis data menggunakan regresi linier berganda. Hasil penelitian menunjukkan secara parsial Return On Equity tidak berpengaruh terhadap Kebijakan Dividen dengan nilai thitung 1,335 < ttabel 2,045, Debt to Equity Ratio tidak berpengaruh terhadap Kebijakan Dividen dengan nilai thitung 0,408 < ttabel 2,045. Sedangkan Current Ratio berpengaruh teerhadap Kebijakan Dividen dengan nilai thitung 2,987 > ttabel 2,045. Secara simultan Return On Equity, Debt to Equity Ratio dan Current Ratio berpengaruh terhadap Kebijakan Dividen dengan nilai Fhitung 3,608 > Ftabel 2,95. Hasil uji koefisien determinasi Return On Equity, Debt to Equity Ratio dan Current Ratio mampu menjelaskan Kebijakan Dividen yaitu sebesar 20,2% sedangkan sisanya 79,8% dijelaskan oleh variabel lain yang tidak dijelaskan dalam penelitian ini. Kata Kunci: Return On Equity, Debt o Equity Ratio, Current Ratio, Kebijakan Dividen